Towards a context-aware framework for pervasive computing authorization management - ARGYROUDIS, PATROKLOS; O'MAHONY, DONAL EDWARD (My University, 2005)
Pervasive computing environments have by definition three main inherent properties; extremely open and dynamic nature, suggesting large number of interactions among previously unknown entities, the ability to adapt according to perceived context information, and interaction interfaces that integrate naturally with the goals users are trying to achieve. Traditional security management approaches fail to capture the requirements of pervasive computing. Our proposed architecture, called ?THER, addresses access control and the establishment of security associations in pervasive environments by extending traditional trust management.We model permissions as the rights of authority sets that grow dynamically without requiring manual reconfigguration, and we definne context-adaptive access control policies that are embedded into pervasive artifacts using the well defined concept of location-limited channels.
PUBLISHED
Keywords: Computer Science